Analysis Of The Influence Of Science In Science Learning In Class V Sds Bina Satria Mulia - Afifah, Cut Fatima Nur; Azzahra, Tsabitah Humairah (Journal of Innovation in Research, Education and Culture (JIREC), 2023)
The formulation of the research problem is as follows : " How approach scientific student on Material Science Learning Properties Light Class V SDS Bina Knight Your Highness ?” This research aims to know influence Approach scientic to Creativity Study Student on Material Science Learning Properties Light Class V SDS Bina Knight Noble. Population used in study This is on student Class V SDS Bina Knight Mulia Medan has 2 classes totaling 50 students . _ The sample used was for the experimental class and the control class, each consisting of 25 students. From the results of the research, data analysis and discussion in the previous chapters, it can be concluded that the approach scientific student on Material Science Learning Properties Light Class V SDS Bina Knight Your Highness is good enough. Students are accustomed to using science in learning activities. Creativity Study Student on Material Science Learning Properties Light Class V SDS Bina Knight His Majesty has been increasing. This can be seen from the increasingly creative students in studying natural science in the material properties of light. There is a positive and significant influence of the scientific approach variable (X) on the student learning creativity variable (Y), meaning that there is a direct influence or relationship between the scientific approach to student learning creativity in a real way. So , school must notice implication between the approach variables scientific to creativity Study student .Keywords : Science , Science Learning